2008
DOI: 10.4161/epi.3.3.6253
|View full text |Cite
|
Sign up to set email alerts
|

A work in progress: The clinical development of histone deacetylase inhibitor

Abstract: It has been widely recognized that histone deacetylases (HDAC) are promising targets in the field of oncology. An impressive body of preclinical research points to the ability of HDAC inhibitors (HDACIs) to modulate a wide variety of cellular functions, including cell differentiation, cell cycle progression, apoptosis, cytoskeletal modifications and angiogenesis. Originally developed as epigenetic drugs because of their ability to inhibit histones deacetylation, HDACIs are now being considered also because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
67
3
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 70 publications
(88 reference statements)
1
67
3
2
Order By: Relevance
“…Although subnanomolar HDAC inhibitors are available, they show poor selectivity among the class I, II, and IV HDACs (Marsoni et al 2008), and although potent sirtuin activators and inhibitors have been reported they also show modest selectivity (Sanders et al 2009). HDAC-specific inhibitors are thus actively being pursued, but obtaining them may be particularly challenging because the class I, II, IV, and class III HDACs each share a highly homologous active site and catalytic mechanism (Marsoni et al 2008).…”
Section: Writers and Readers Of Histone Acetylationmentioning
confidence: 99%
“…Although subnanomolar HDAC inhibitors are available, they show poor selectivity among the class I, II, and IV HDACs (Marsoni et al 2008), and although potent sirtuin activators and inhibitors have been reported they also show modest selectivity (Sanders et al 2009). HDAC-specific inhibitors are thus actively being pursued, but obtaining them may be particularly challenging because the class I, II, IV, and class III HDACs each share a highly homologous active site and catalytic mechanism (Marsoni et al 2008).…”
Section: Writers and Readers Of Histone Acetylationmentioning
confidence: 99%
“…[5,6] In cancerous states, abnormal HDAC activity can lead to aberrant expression of genes regulating cell proliferation, cell cycle, and apoptosis and transcriptional repression of tumor suppressor genes. [3,7] Furthermore, HDACs are known to regulate the acetylation (and thus function) of various non-histone proteins important for cell growth and differentiation, including tumor suppressors. [3,8] Human HDACs are subdivided into 4 classes.…”
Section: Histone Deacetylases: Overview and Inhibition In Cancermentioning
confidence: 99%
“…This data provided the structural basis for the catalytic mechanism and the inhibition of this family of enzymes, paving the way for the design of new bioactive molecules able to interfere with the deacetylation reaction. Several compounds targeting HDACs entered clinical trials in the last year and have been reviewed elsewhere [98,105,139,141,234,237,[240][241][242][243]. These proteins belong to the open / folding class, with an eight-stranded parallel -sheet sandwiched between -helices.…”
Section: Class I Ii and Iv Deacetylasesmentioning
confidence: 99%